f(b)-f(a)/b-a = f'(c) MVT
to find f(b) and f(a), just plug endpoints into original function
f(b) = f(4) = (2/3)
f(a) = f(1) = (1/3)
----------- = f'(c)
4 - 1
(1/9) = f'(c)
next, find derivative of f(x)
f'(c) = f'(x)
(1/9) = (x)(x+2)^-1
(1/9) = (x+2)^-1 - x(x+2)^-2
(1/9) = (1/x+2) - (x/(x+2))^2
(1/9) = (1/x+2) * (1 - (x/(x+2))
(1/x+2) = (1/9) mult. ea s. by 9
(9/x+2) = 1
9 = x + 2
7 = x
I'm sure you can solve the other x
Calculus - verify that the function satisfies the three hypotheses of rolle's ...
Calculus-Function - sketch the graph of a function in neighborhood x=2 that ...
Calculus - Can someone please work this algebra. verify that y(x) = -ln (x - cx^...
calculus - Let be a function that satisfies
Calculus - Let h(x) be a function which satisfies h'(4) = 3. If k(x) = h(x2), ...
math - Verify that the function f(x)=x^3-6x^2+8x+4 satisfies the three ...
calculus - sketch graph of a function f that is differentiable and that ...
math - verify that the function satisfies the hypothesis of the mean value ...
calculus - Find a formula for the exponential function that satisfies h(2)=22 ...
calculus - verify that y=c/x^2 is a general solution of the differential ...